Recent Progress on Carbon Quantum Dots Based Photocatalysis - Jung, Hwapyung; Sapner, Vijay S.; Adhikari, Arindam; Sathe, Bhaskar R.; Patel, Rajkumar (Frontiers in Chemistry, 2022)
As a novel carbon allotrope, carbon quantum dots (CQDs) have been investigated in various fields including photocatalysis, bio imaging, optoelectronics, energy and photovoltaic devices, biosensing and drug delivery owing to their unique optical and electronic properties. Especially, CQDs’ excellent sunlight harvesting ability, tunable photoluminescence (PL), up-converted photoluminescence (UCPL) and efficient photo-excited electron transfer have enabled their applications in photocatalysis. This work focuses on the recent progress on CQDs related materials’ synthesis, properties and applications in photocatalysis.